Crystal structure of tetrameric human Rabin8 GEF domain. Issue 4 (29th January 2018) - Vetter, Melanie; Boegholm, Niels; Christensen, Anni; Bhogaraju, Sagar; Andersen, Marie B.; Lorentzen, Anna; Lorentzen, Esben
Abstract: Rab GTPases and their effectors, activators and guanine nucleotide exchange factors (GEFs) are essential for vesicular transport. Rab8 and its GEF Rabin8 function in formation of the cilium organelle important for developmental signaling and sensory reception. Here, we show by size exclusion chromatography and analytical ultracentrifugation that Rabin8 exists in equilibrium between dimers and tetramers. The crystal structure of tetrameric Rabin8 GEF domain reveals an occluded Rab8 binding site suggesting that this oligomer is enzymatically inactive, a notion we verify experimentally using Rabin8/Rab8 GEF assays. We outline a procedure for the purification of active dimeric Rabin8 GEF‐domain for in vitro activity assays.